Pengembangan Media Pembelajaran E-Comic pada Mata Pelajaran PPKn Kelas VIII SMP - Zuliasmi, Syahra; Anugrah, Septriyan; Novrianti, Novrianti; Masnur, Alkadri (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to test the validity, practicality, and effectiveness of E-Comic media in the Civics Education learning for eighth-grade junior high school students. This study uses the research and development (R&D) method with a simplified Borg and Gall model into three stages: preliminary study, product development and validation, and effectiveness testing. The instruments used are validation sheets and tests in the form of multiple-choice questions. The data produced are analyzed quantitatively descriptive. The E-comic media developed is considered feasible with a material validation of 4.73 and a media of 4.80. The practicality was high (4.69) and the effectiveness was sufficient (N-gain 65.74%). The presentation is engaging, accessible, and enhances students' interest and understanding. Although effective, this media is still limited to one chapter of material and tested in one school so it needs further development. The results of the development of E-comic media in PPKn learning have proven to be valid, practical, and quite effective in improving student learning outcomes. This medium makes it easier to understand material through attractive and accessible visuals. However, the scope of the material is still limited and needs further development so that it can be applied more widely in various schools